MANAJEMEN ASUHAN KEBIDANAN KESEHATAN REPRODUKSI PADA NY “N” DENGAN ANEMIA PADA WANITA PRAKONSEPSI DI RSUD LABUANG BAJI MAKASSAR - Iskandar, Irmayanti; Al Kautzar, Anieq Mumthiâ€™ah; Alza, Nurfaizah (Jurnal Midwifery, 2022)
Introduction Preconception is the period before pregnancy or prior to the meeting of the ovum with sperm. Adequate nutrition intake during the preconception will support the functional reproductive system as it smoothens the process of ovum maturation, ovum production, and ovum quality and complete fertilization process. Anemic preconception puts women at a higher risk of anemia in pregnancy, which eventually impacts on the fertilization process and fetal development. This study aimed to conduct the management of reproductive health midwifery care on Mrs. “N” with preconception anemia in Regional Public Hospital of Labuang Baji Makassar. Method This research in accordance with the 7-step Varney. Result The findings suggest that Mrs. “N” reported several complaints including fatigue, frequent dizziness, pale conjunctiva appearance, dry lip mucosa, and Hb 11.9 g/dl as shown from the laboratory results. The midwifery care was conducted by providing the patient with iron tablets containing 60 mg of elemental iron and 250 folic acids. In addition to that, the medical team also gave a recommendation that the patient consume date juice as well as 7 pieces of dates every morning. Conclusion This study concluded the midwifery care using the 7-step Varney and SOAP for Mrs. “N” with preconception anemia in Regional Public Hospital of Labuang Baji Makassar with results of increasing Hb levels up to 15.8 gr/dl, composmentis awareness, normal vital signs, and no abnormalities nor complications shown from the physical examination. These results show that there is no gap between all the treatments and the theories.